2010
DOI: 10.3109/00365521.2010.533380
|View full text |Cite
|
Sign up to set email alerts
|

Serum fatty acid profile in subjects with irritable bowel syndrome

Abstract: Although organic disease has been ruled out in patients with IBS, they presented signs of inadequate supply of long-chain fatty acids. Supplementation with n-3 fatty acids may be implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
3
26
0
2
Order By: Relevance
“…A recent study indicates a relative deficiency of polyunsaturated long-chain fatty acids (LCFA) in patients with IBS [87], constituting another rationale for supplying n-3 polyunsaturated fatty acid-rich seal oil to this patient population.…”
Section: Therapeutic Trials: Pilot Studies With Seal Oilmentioning
confidence: 99%
“…A recent study indicates a relative deficiency of polyunsaturated long-chain fatty acids (LCFA) in patients with IBS [87], constituting another rationale for supplying n-3 polyunsaturated fatty acid-rich seal oil to this patient population.…”
Section: Therapeutic Trials: Pilot Studies With Seal Oilmentioning
confidence: 99%
“…Intestine is the main place to absorb fatty acids and -3 PUFAs absorption in intestine is limited by a variety of conditions, including the composition of fatty acids in diet, the body itself and existing form of fatty acids. Solakivi et al analyzed the contents and types of PUFAs in serum of 32 patients with irritable bowed syndrome (IBS) and 59 healthy controls and found that the serum DHA content of IBS patients was significantly decreased (Solakivi et al, 2011). These suggested that the absorption capacity of DHA in intestine of IBS patients was changed.…”
Section: Diet Gut Microbiota and Admentioning
confidence: 99%
“…A retrospective review of capsule endoscopies for suspected small bowel bleeding demonstrated that combination of low-dose aspirin and thienopyridine drugs (ticlopidine and clopidogrel) may exacerbate small bowel injury [7]. Inadequate supply of long-chain fatty acids was found in subjects with IBS [8]. Organic disease had been ruled out and intestinal malabsorption was suggested by the authors although no mechanism behind this is clear at the present time.…”
Section: This Month In Scandinavian Journal Gastroenterologymentioning
confidence: 94%